The effectiveness of egra technique to improve students' writing skills - Gede Eka Wahyu; Ni Putu Evi Wahyu Citrawati (Journal of Applied Studies in Language, 2022)
This study aims to discover the increase in students' ability to write essays in English. It is a class action research that administered the EGRA technique in the learning process. This study involved two classes, namely the control class and the experimental class as the research sample. The qualitative descriptive method was used in analyzing the data. The data analyzed are presented in graphs and tables and then described qualitatively. Several theories are used in this study, such as error analysis, writing descriptive text, and EGRA techniques. The pre-test results showed the highest grammatical error score of control class results was 5.1, while the lowest score of students' grammatical errors was 2.8. After getting learning actions with conventional methods, there was a decrease in grammatical errors, the highest score was 3.4, while the lowest was 1.8. Meanwhile, the pre-test result of the experiment class showed the highest error score was 6.6, and the lowest score was 1.2. After the treatment administered with the EGRA technique, there is a decrease in grammatical errors, the highest score is 3.3, and the lowest score is 1.6. With the application of the EGRA technique in classroom learning, the student's grammatical ability increases, and students are more active and enjoyable in the learning process.